Equilibrium clusters in suspensions of colloids interacting via potentials with a local minimum - Baumketner, A.; Cai, W. (Condensed Matter Physics, 2016)
In simple colloidal suspensions, clusters are various multimers that result from colloid self-association and exist in equilibrium with monomers. There are two types of potentials that are known to produce clusters: a) potentials that result from the competition between short-range attraction and long-range repulsion and are characterized by a global minimum and a repulsive tail and b) purely repulsive potentials which have a soft shoulder. Using computer simulations, we demonstrate in this work that potentials with a local minimum and a repulsive tail, not belonging to either of the known types, are also capable of generating clusters. A detailed comparative analysis shows that the new type of cluster-forming potential serves as a bridge between the other two. The new clusters are expanded in shape and their assembly is driven by entropy, like in the purely repulsive systems but only at low density. At high density, clusters are collapsed and stabilized by energy, in common with the systems with competing attractive and repulsive interactions. В простих колоїдних розчинах кластерами називаються мультимери, що виникають внаслiдок асоцiацiї
мономерiв i спiвiснують з ними в динамiчнiй рiвновазi. Iснують два типи потенцiалiв, що ведуть до утворення кластерiв: а) потенцiали з глобальним мiнiмумом, що можуть виникнути, зокрема, внаслiдок неповної компенсацiї притягальної взаємодiї на коротких вiдстанях та вiдштовхувальної взаємодiї на довгих
вiдстанях, б) повнiстю вiдштовхувальнi взаємодiї, якi демонструють м’яке “плече”. За допомогою комп’ютерних симуляцiй в данiй роботi показано, що потенцiали з локальним мiнiмумом i вiдштовхувальним
хвостом теж мають здатнiсть утворювати рiвноважнi кластери. Хоча вони не належать до жодного з перелiчених вище класiв, аналiз показує, що такi потенцiали мають з ними певнi спiльнi характеристики.
При малiй густинi колоїдiв кластери, утворенi новими потенцiалами, видовженi подiбно до кластерiв в
суто вiдштовхувальних системах. При великiй густинi, новi кластери компактнi, як це спостерiгається в
системах з глобальним потенцiальним мiнiмумом. Отже, новi потенцiали слугують тим мiстком, який поєднує два вiдомi класи потенцiалiв, що ведуть до утворення кластерiв в колоїдних розчинах.